PERCEPTION AND ROLE OF THE COMMUNITY IN DEVELOPING URBAN FOREST IN PONTIANAK CITY - Purba, Gunawan Frando; Fahrizal, .; Siahaan, Sarma (Universitas Tanjungpura, 2017)
The Forest areas around Bansir Laut village and Benua Melayu Darat village have a high diversity of plants tree. Developing urban forests can be an alternative in addressing environmental problems. Urban forests can be used as a biodiversity collection that spread throughout the territory of the country and place for water reserve. This research aimed to know the perception and role of the community in developing the forest in Pontianak city, West Kalimantan. The methods for data collection were conducted by interviews, questionnaire distributed to respondents. The respondent were selected using purposive sampling method. The result showed that the public perception of the urban forest was in the high category by 54 respondents or 58.07%, in the medium category by 27 respondents or 29.03%, and in the low category by 12 respondents or 12.90%. The public perception of the urban forest was enthusiastic and very supportive to its development in order to be used sustainably. The comunity role to urban forest is utilize the urban forest according to the Law No. 32 / 2009 on the protection and management of the environment. Keywords: Community Role, Public Perception, Urban Forest Development